Analisis Strategi Pengembangan Bisnis pada Kolam Ikan Aba di Kecamatan Rengat Kabupaten Indragiri Hulu Provinsi Riau - Warnadi Warnadi; Muhklas Adi Putra; Said Afriaris (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Rengat, which is mostly located in the Indragiri River, has great potential in developing fish cultivation and rearing businesses which can be done in various ways, of course by utilizing the availability of water so that it is economically valuable. The research method used is a qualitative descriptive analysis type of research using data collection techniques through interviews, observation and documentation. The results of this research indicate that it is necessary to develop the distribution of cultivation products, especially expanding the freshwater fish market segment so that productivity can be optimized and also protect the waters along the Indragiri River in Indragiri Hulu Regency, Riau Province.